Faktor yang Memengaruhi Distress Psikologis pada Pekerja Rantau: Tinjauan Sistematik - Shella Shella; Tulus Winarsunu; Nida Hasanati (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This systematic review aims to identify the main factors influencing psychological distress in migrant workers. Referring to the PRISMA guidelines and the SPIDER framework, this study analyzed 10 articles that met the criteria from a total of 500 literature sources found through Google Scholar over the past five years. The synthesis results indicate that psychological distress is caused by a complex relationship between work, economic, social, and individual psychological factors. Work factors include long working hours and involvement in precarious work (3D). From an economic perspective, income instability and the stress of remittances are sources of chronic anxiety. Social factors such as discrimination, isolation, and language barriers also exacerbate mental health conditions. Individual characteristics such as low resilience, young age, and low education are strongly correlated with stress vulnerability. This study concludes the need for more comprehensive mental health protection policies for migrant workers at the international level.